The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1121/1.2933777
|View full text |Cite
|
Sign up to set email alerts
|

Use of noise and vibration signal for detection and monitoring of cavitation in kinetic pumps

Abstract: Cavitation in kinetic pumps causes lowering performance, mechanical damage and increase of vibrations and noise. Therefore, it is important to detect inception and development of cavitation phenomenon in the pump. This paper deals with signals of vibrations and noise, which will be used for detection and monitoring of cavitation in kinetic pumps, and also to prevent the effect of cavitation in the pump and pumping system. When the cavitation is increasing, the flowing conditions are changing, which leads to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Cernetic et al [5] studied two centrifugal pumps; pump A made of metal alloy with 6 blades closed impeller. Pump B made of plastic material with 6 blades semi-open impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Cernetic et al [5] studied two centrifugal pumps; pump A made of metal alloy with 6 blades closed impeller. Pump B made of plastic material with 6 blades semi-open impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The trend of the Welch estimator is similar with those presented in other works [12, 14 & 15] at the same frequency range, with the use of microphones. At the range of 0-3 kHz the amplitude differences are indiscernible due to the cavitation interaction with the low frequency mechanical noise caused mainly by the BPF and its harmonics [15]. However, at higher frequencies those harmonics become weaker and the broadband noise increases due to a more pronounced cavitation effect (Figure 8).…”
Section: Ae and Vibration Measurements 331 Vibration Band Power Invmentioning
confidence: 97%
“…Similarly to [12], three different discrete tones were selected for each impeller and all of them appeared at a sharper increase than the total noise level curve. Cernetic et al [15] presented the variation of the total head and relative amplitude of vibrations with the NPSH for two different pumps, one with a metallic closed impeller and one with a plastic semi-open impeller. The vibration results for the two impellers are for different frequencies; the metallic impeller is for a frequency band around 1600 Hz and the plastic for the discrete frequency of 148 Hz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main types of cavitation (partial attached cavities, travelling bubble cavitation, vortex cavitation and shear cavitation) were presented. Cernetic et al (2008) performed experimental work using signals of vibration and noise which used for detection and monitoring of cavitation in kinetic pumps. Their experimental results indicated that when cavitation is fully developed, the measured signals at a characteristics frequency or range of frequencies start decrease.…”
Section: Introductionmentioning
confidence: 99%